Translating Transitivity of Indonesian Tourism Texts and Its English Translation : A Case in Madura - Sriyono Sriyono (Makassar State University, 2021)
Abstract. This research aims at investigating the translation of the transitivity system of Madura tourism texts from Indonesian as the Source Text (ST) into English as the Target Text (TT). Besides, this also purposes to study how the transitivity as the representation of experiential meaning in tourism texts is realized and translated. The method used in this research is qualitative descriptive, while the data were taken from tourism texts of promotional media in Madura. Accordingly, Systemic Functional Linguistics (SFL) is pondered as a tool to identify the transitivity system and its translation of tourism promotion media in Madura. This study shows that the transitivity in tourism texts is translated differently which results in the realization of experiential meaning expression between ST and TT. Most of the experiential meaning in ST are realized with the relational process and as well as in the TT. Transposition and modulation in terms of translation technique also influence the differences of the understanding of readers (tourists) to the object promoted in Madura. Therefore, the process and participant in the transitivity system found ST and TT also generates the dissimilarities interpretation of experiential meaning and point of view in Indonesian tourism texts and its English translation. Keywords: transitivity; translation; tourism texts